Transformasi Teori Belajar Kecerdasan Majemuk dan Implikasinya dalam Konteks Pendidkan Agama Kristen - Lois Gamerakai; Yordin Benu; Melisa Boimau; Maria Indriani Sesfao (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
Intelligence is the ability to learn from experience and acquired knowledge to adapt and adjust to the environment. Intelligence is not only measured through cognitive thinking ability but also through various potentials known as multiple intelligences. Howard Gardner’s theory of multiple intelligences emphasizes that individuals possess diverse capacities that cannot be assessed solely through traditional intelligence measures. According to the Indonesian Dictionary, intelligence refers to cleverness, intellectual development, and sharpness of thought. Previous research by Sumiati shows that the application of multiple intelligences in learning at Charis Institute Elementary School supports optimal classroom learning through varied instructional methods. This study aims to examine the application of multiple intelligences theory in Christian education in Indonesia, particularly in learning that emphasizes multiculturalism and character development. The research method used is a literature study with descriptive analysis of relevant academic sources and educational practices. The results indicate that the implementation of multiple intelligences can improve learning quality through varied strategies, more comprehensive assessment systems, and integration of cultural and spiritual values. Teacher training and valid assessment instruments are essential for effective implementation. In conclusion, multiple intelligences offer an alternative to traditional approaches and strengthen inclusive, contextual, holistic, creative, and character-based education outcomes.